Derechos Humanos y Salud: El caso del VIH/SIDA. - UGARTE GIL, Cesar Augusto; MIRANDA MONTERO, J. Jaime (Revista Médica Herediana, 2013)
The history of HIV/AIDS (Human Immunodeficiency Virus/ Acquired Immunodeficiency Syndrome) has shown us, continuously, many experiences in the political, moral, economic, social, therapeutic and clinical areas, amongst others. Due to the various and diverse implications of this complex problem, a solitary analysis framed by only one of those fields results difficult and inappropriate. We argue that a human rights approach should be undertaken to understand and address this problem. The advantage of this type of analysis goes beyond clinical aspect of the patient, and thus provides an integral vision that every health professional should handle in a day-to-day basis.